UAW supporters march in Santa Maria - Manuel Echavarria::::::photographer:::
Local UFW members and supporters march down Main Street near West Alvin St. in Santa Maria. Partidarios y miembros locales de la UFW desfilan en la calle Main, cerca del oeste de la calle Alvin, en Santa Maria.